Biocompatibility of an apical ring plug for left ventricular assist device explantation: Results of a feasibility pre‐clinical study. Issue 5 (24th December 2021) - Mariani, Silvia; Li, Tong; Hegermann, Jan; Bounader, Karl; Hanke, Jasmin; Meyer, Tanja; Jannsen‐Peters, Heike; Haverich, Axel; Schmitto, Jan D.; Dogan, Günes
Abstract: Background: Patients receiving left ventricle assist devices (LVADs) as bridge to recovery remain a minority with 1%–5% of LVADs explanted after improvement of myocardial function. Nevertheless, considering the growing population of patients supported with LVADs, an increasing demand of new explantation strategies is expected in the near future. A novel plug for LVAD explantation has been developed and its biocompatibility profile needs to be proved. This study tested the biocompatibility of this novel plug in an in vivo ovine model. Methods: Six adult Blackhead Persian female sheep received plug implantation on the cardiac apex via minimally invasive approach and were clinically observed up to 90 days. Echocardiography was performed to detect thrombus formation or further plug‐related complications. After the observation period, euthanasia was performed and samples including the plug and the surrounding tissues were obtained to be analyzed with correlative light and electron microscopy. Organ necrosis, ischemia and peripheral embolism were investigated. Results: Three animals survived surgery and completed the follow‐up time without experiencing clinical complications. Echocardiographic controls excluded the presence of an intracavitary thrombus in the left ventricle (LV). Autopsy confirmed no signs of local infection, LV thrombus or peripheral embolism. Light and electron microscopy revealed an intact epithelium covering a layer of connective tissue on the plug surface facing the heart lumen. Conclusions: This novel apical plug for LVAD explantation allows for endothelial and connective tissue growth on its ventricular side within 90 days from surgery. Further studies are required to fully demonstrate the biocompatibility of this apical plug and investigate the optimal anticoagulation regimen to be applied after implantation. Abstract : A novel metal apical ring plug for LVAD explantation was implanted and followed‐up for 3 months in 3 Blackhead Persian female sheep. Follow‐up was uneventful with no signs of local infection, ventricular thrombus or peripheral embolism. Light and electron microscopy revealed an intact epithelium covering a layer of connective tissue on the plug surface facing the heart lumen. Further studies are required to fully demonstrate the biocompatibility of this apical plug and investigate the optimal anticoagulation regimen after implantation.